Nimonol from Chisocheton macrophyllus (Meliaceae) Seeds and Their Cytotoxic Activity against P-388 Leukaemia Cells - Nurlelasari Nurlelasari; Desi Harneti P. Huspa; Rani Maharani; Darwati Darwati; Tri Mayanti; Kindi Farabi; Muhammad Hanafi; Unang Supratman (Syarif Hidayatullah State Islamic University, 2022)
The Chisocheton genus belongs to the Meliaceae family which produces various structures and activities of compounds, such as antimalarial, antimicrobial, antitumor, anti-inflammatory, and cytotoxic. This plant has 53 species that are spread in tropical and sub-tropical forests, including Indonesia. Chisocheton plants have been known as plants that produce limonoids, namely triterpenoid compounds that have been modified to lose four terminal carbons (tetranortriterpenoids). One of the species whose phytochemical reports are still few and interesting for research on limonoid content is Chisocheton macrophyllus. Chisocheton macrophyllus is a tall plant that grows in the rainforest in the northern part of the island of Sulawesi, Indonesia, has the regional name ma aa, gula, pasak lingga, gending, ta suea, bekak, or pithraj tree. This paper will describe a limonoid compound, namely nimonol which has been isolated from Chisocheton macrophyllus. Nimonol is known to have the molecular formula C28H36O5 from a group of havanensin. The structure was determined by spectroscopic methods UV, IR, 1D-NMR (1H-NMR, 13C-NMR, and DEPT), 2D-NMR (1H-1H COSY, HMQC, and HMBC), and mass spectroscopy.